2004
DOI: 10.1002/app.20604
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure of polysiloxane liquid crystalline elastomers with a mesogenic crosslinking agent

Abstract: ABSTRACT:A new mesogenic crosslinking agent M-1 was synthesized to minimize the perturbations of a nonmesogenic crosslinking agent for liquid crystalline elastomers. The synthesis of new side-chain liquid crystalline elastomers containing a rigid mesogenic crosslinking agent M-1 and a nematic monomer M-2 is described by a one-step hydrosilylation reaction. The chemical structures of the obtained monomers and elastomers were confirmed by 1 H NMR and FTIR spectroscopy. The mesomorphic properties and phase behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…They discussed the effect of mechanical deformation on the mesophase stability, and found an increase of the phase transformation temperature with stress as predicted by Landau-de Gennes theory [14][15][16]. Since then, a wide range of synthetic side-chain elastomers have been described in literature [17][18][19][20][21]. 0032 On the other hand, fewer papers were published on the synthesis and characterization of main-chain LCEs [22][23][24][25].…”
Section: Introductionmentioning
confidence: 98%
“…They discussed the effect of mechanical deformation on the mesophase stability, and found an increase of the phase transformation temperature with stress as predicted by Landau-de Gennes theory [14][15][16]. Since then, a wide range of synthetic side-chain elastomers have been described in literature [17][18][19][20][21]. 0032 On the other hand, fewer papers were published on the synthesis and characterization of main-chain LCEs [22][23][24][25].…”
Section: Introductionmentioning
confidence: 98%
“…Many functional properties of LCEs rely on the reversible anisotropic–isotropic transition associated with LC order. Numerous studies have shown that T i can be correlated to the cross‐link density in hydrosilylation‐based LCE systems . High cross‐link densities of the network can disrupt the heat fusion and lower T i , leading to a less stable liquid‐crystalline phase, where lightly cross‐linking hardly affects T i .…”
Section: Introductionmentioning
confidence: 99%
“…The mesomorphic monomer M‐2 was synthesized according to our previously reported paper 31. White crystalline was obtained (mp: 135 °C, yield: 91%).…”
Section: Methodsmentioning
confidence: 99%